Implementation Of Student Management In Improving The Quality Of Graduates At Sigli Uggul Education Foundation Foundation (YPPU) - Nadhifah, Nadhifah; AR, Murniati; Ismail, Ismail; Binti Zakaria, Nurhijrah (Jurnal Ilmu Pendidikan, 2024)
Student management is organizing and managing students from the moment they are accepted until they graduate. The quality of graduates is an indicator of a school's success. The aim of this research is to find out in depth about the Implementation of Student Management in Improving the Quality of Graduates at Unggul SMP Unggul Community Development Education Foundation (YPPU) Sigli, Sigli Regency. This research uses a qualitative approach with descriptive research type. Data collection techniques use observation, interviews and documentation. The data analysis technique used is qualitative descriptive analysis with data reduction techniques, data presentation and drawing conclusions. Based on research findings, it was found that: (1) Student management planning is carried out through needs analysis withhow to measure student capacity, form a committee for accepting new students and disseminating information through brochures, banners and socialization, selecting students through administrative selection, academic selection, Al-Qur'an reading selection, interview selection, and orientation through mass activities Introduction to the School Environment (MPLS); (2) Implementation of student management, namely placement of students using a heterogeneous system, guidance and development of students in academic and non-academic aspects through extracurricular activities and additional study guidance; (3) Evaluation of student management is carried out by means of discussion, supervision and monitoring of student learning. Recording and reporting student assessments; (4) Constraints in student management include cheating in the recruitment process, obstacles in dealing with different levels of ability, interest and motivation of students, and limited involvement of alumni.